Interventional Efects of the Topical of “Sanse Powder” Essential Oils Nanoemulsion on Knee Osteoarthritis in Rats by Targeting the ERS/TXNIP/NLRP3 Signaling Axis - Liu, Zixiu; Liao, Taiyang; Yang, Nan; Ding, Liang; Li, Xiaochen; Wu, Peng; Wang, Peimin (Frontiers in Pharmacology, 2021)
Purpose: Our recent research is dedicated to finding effective drugs for the treatment of knee osteoarthritis (KOA) from traditional Chinese medicine and trying to make full use of modern science and technology to uncover the mechanisms and targets behind them. Synovial inflammation is one of the key pathological features of KOA, and a growing number of researchers realize that early intervention of synovial inflammation may be able to reverse disease progression. The close association of traditional natural products with modern nanotechnology may be important for improving the anti-synovitis efficacy. The purpose of our research was to explore the anti-synovitis mechanism of NEs-SP-EO that might be associated with the ERS/TXNIP/NLRP3 signalling axis. methods: Chemical composition of “Sanse Powder” essential oil (SP-EO) and NEs-SP-EO were analyzed by GC-MS. NEs-SP-EO were prepared and characterized by nanoparticle tracking analysis, polydispersity index (PDI), zeta potential (ZP), ultraviolet-visible spectroscopy, and transmission electronic microscopy. The CCK8 assay for cell viability of NEs-SP-EO was performed on fibroblast-like synovial cells (FLSs) and the inflammatory environment was stimulated by LPS to explore the therapeutic mechanisms in vitro. Experiments of NEs-SP-EO in vivo were performed in male SD rats. Results: The GC-MS results showed that 30 compounds were present in SP-EO and 11 components of NEs-SP-EO were identified. The results also showed that the formulation of NEs-SP-EO exhibited suitable particle size, negative charge, and stable system. In vitro and vivo testing, NEs-SP-EO produced anti-synovitis efficacy by reduced the induction of the ERS/TXNIP/NLRP3 signaling axis as well as regulating the overproduction of IL-1β、IL-18. Conclusion: We have developed a new type of essential oil nanoemulsion from “Sanse Powder” and demonstrated that it can managing synovitis of KOA. Besides, we have initially explored the anti-inflammatory mechanism that may be related to the ERS/TXNIP/NLRP3 signaling axis.